2011
DOI: 10.1055/s-0031-1295463
|View full text |Cite
|
Sign up to set email alerts
|

OPG-Fc Treatment in Growing Pigs Leads to Rapid Reductions in Bone Resorption Markers, Serum Calcium, and Bone Formation Markers

Abstract: Inhibition of the receptor activator of NF-κB ligand (RANKL) is a novel therapeutic option in the treatment of osteoporosis and related diseases. The aim of this study was to evaluate bone metabolism and structure in pigs after RANKL inhibition. 12 growing pigs were assigned to 2 groups with 6 animals each. The OPG group received recombinant human OPG-Fc (5 mg/kg IV) at day 0, the control group was given 0.9% NaCl solution. Serum levels of OPG-Fc, calcium (Ca), phosphorus (P), and bone turnover markers were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…When using swine as a model for studying effects of alcohol drinking on bone, especially similarities concerning bone physiology are of crucial importance. Our group showed that porcine bone marrow stromal cells express a cytokine pattern including the RANK/RANKL/OPG system comparable to human and murine cells (Sipos et al., , b). Moreover, bone remodeling, the process responsible for maintaining bone integrity and mineral homeostasis, has been described to be similar to humans.…”
Section: Discussionmentioning
confidence: 87%
“…When using swine as a model for studying effects of alcohol drinking on bone, especially similarities concerning bone physiology are of crucial importance. Our group showed that porcine bone marrow stromal cells express a cytokine pattern including the RANK/RANKL/OPG system comparable to human and murine cells (Sipos et al., , b). Moreover, bone remodeling, the process responsible for maintaining bone integrity and mineral homeostasis, has been described to be similar to humans.…”
Section: Discussionmentioning
confidence: 87%
“…Cell types are identified due to their morphological characteristics and position within specific bone compartments. Porcine bone marrow-derived stromal cells as well as osteoblasts and osteoclasts exhibit similar in vitro growth characteristics and osteoimmunological properties as their rodent and human counterparts ( 51 , 52 ).…”
Section: Osteoimmunology Of Hypoparathyroidismmentioning
confidence: 94%
“…The reasons for that could be a generally higher bone mineral density in pigs when compared to humans and also an (at least partial) extragonadal estrogen synthesis, which plays OVX off against the desired hypoestrogenism [6]. On the other hand, bone architecture and metabolism clearly react to osteoimmunological measures as expected at least in adolescent commercial pigs, as shown for OPG [9]. Our group used this observation to test pigs aged 2-4 months as a model for a type of secondary osteoporosis, namely alcohol-induced osteoporosis [10].…”
mentioning
confidence: 95%
“…a decrease of bone resorption (and formation due to coupling effects) markers and serum calcium levels. Additionally, μCT analyses demonstrated an improvement of specific architectural indices and bone mineralization at selected bone sites [9]. Research with OPG led to the development of denosumab, which is a fully humanized monoclonal antibody against RANKL and licensed for the treatment of osteoporosis with an elevated risk for fractures in post-menopausal women as well as in men.…”
mentioning
confidence: 99%